Life cycle assessment of agro-industrial residues valorization processes to obtain phenolic-rich extracts - Carpentieri, Serena; Ghanem, Antoine; Khwaldia, Khaoula; Silva, Ana Sanches; Ferrari, Giovanna (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe valorization of agrifood residues into phenolic-rich extracts represents a promising approach to reduce residues and recover resources within a circular economy framework.MethodsIn this study, a comparative Life Cycle Assessment (LCA) of three extraction processes from agrifood by-products was conducted, namely date pits powder, citrus by-products, and cherry press-cake, producing phenolic-rich extracts to be applied in packaging, food, and cosmetic products. Using the ReCiPe 2016 method and a functional unit of 1 kg of total phenolic compounds (TPC), environmental impacts across 18 categories were assessed from a gate-to-gate perspective.Results and discussionThe extracts from date pits powder, citrus by-products, and cherry press-cake showed TPC of 243 ± 5.6 mg GAE/g extract, 33.57 ± 0.07 mg GAE/g extract, and 445 ± 5 mg GAE/g extract, respectively. Results identified electrical energy consumption as the dominant contributor to environmental burdens in all scenarios, due to the energy-intensive steps of freeze-drying and chemical treatments. The citrus by-products scenario exhibited the lowest environmental impacts due to simplified processing and effective ethanol recovery, despite the total biomass valorization not being considered. In contrast, the cherry press-cake upcycling pathway showed the highest environmental footprint, primarily due to the cascade extraction method implemented. Date pits powder valorization presented an intermediate trend, where the high resource usage was balanced with the total valorization of the biomass to obtain cellulose nanocrystals (CNC). The findings highlight a critical trade-off between environmental performance and resource efficient use, emphasizing the need for the individuation of alternative unit operations, focusing particularly on the reduction of energy usage, to enhance the sustainability of biomass valorization processes in view of their industrial application.